Orientasi Pragmatis dan Idealis dalam Pendidikan Islam: Kajian Kurikulum Madrasah Aliyah Nurul Qur’an Simo Boyolali - Sumadi, Eko (Pascasarjana IAIN Kudus, 2022)
The formulation of the problem that will be answered in this article is how do the leaders and managers of MA Nurul Qur'an respond and answer future challenges through curriculum innovations and educational programs held? This study uses qualitative methods, with 7 respondents, namely; the leader of the pesantren (kyai), the head of the MA, the deputy head of the curriculum, the teacher, and 3 students. Data collection techniques in the form of interviews, observation, and documentation. The data analysis techniques include data reduction, data presentation, and verification or concluding. The discussion in this article concludes, that as a pesantren-based madrasa, the manager of MA Nurul Qur'an is committed to educating students (Santri) so that they can grow into the Upper Middle Class through three alumni profiles, becoming: Kyai, Priyai, and Entrepreneur. The three profiles are a top priority considering that future challenges for alumni will be more complex and require skills and specialization in certain areas of expertise. To encourage the creation of graduates with three alumni profiles, MA Nurul Qur'an made many modifications and developments to the curriculum based on Islamic boarding school values while also emphasizing the strengthening of foreign languages. Academically, this article contributes to providing an argument that the values of idealism and pragmatism can be combined as the basis for the development of Islamic educational institutions. While practically, this article contributes to providing an example for academics and education practitioners, regarding how the madrasa curriculum model is designed to accommodate the interests of idealism and pragmatism.